Effects of Vaccination Against Influenza, Pertussis, and COVID-19 on Human Milk Antibodies: Current Evidence and Implications for Health Equity - Hunagund, Soumya; Golan, Yarden; Asiodu, Ifeyinwa V.; Prahl, Mary; Gaw, Stephanie L. (Frontiers in Immunology, 2022)
Human milk contains three antibody classes that confer mucosal immunity to the breastfed infant: secretory IgA (SIgA), secretory IgM (SIgM), and IgG. Influenza and pertussis vaccines administered during pregnancy induce pathogen-specific SIgA and IgG responses in human milk that have been shown to protect the breastfed infant from these respiratory illnesses. In addition, mRNA vaccines against the SARS-CoV-2 virus administered during pregnancy and lactation induce anti-SARS-CoV-2 IgG and IgA responses in human milk. This review summarizes the immunologic benefits of influenza, pertussis, and COVID-19 vaccines conferred by human milk. Additionally, future research direction in human milk immunity and public health needs to improve lactational support are discussed.